Kamusal Binaların Dijital Sergileme Alanlarına Dönüşmesi: Mapping Projeleri - Tekin, Elvan (Mer Ak Mersin Akademi Danışmanlık Anonim Şirketi, 2021)
[TR] 21. yüzyılın dijital tasarımları yeni sergileme biçimlerine de ilham kaynağı olmuştur. Mekânlardan sokağa taşan sergiler, günümüzde farklı bir boyuta taşınarak kamusal binaların duvarlarında kendilerine yer bulmaya başlamıştır. Bunun en önemli örneklerini ise “Mapping” projelerinde görmek mümkündür. Mapping projeleri, seçilen sergileme alanının fiziksel özellikleri gözetilerek, mekâna uyarlanan 3B dijital tasarımlar olarak adlandırılmaktadır. Mapping uygulamalar, kamusal binaların yüzeyinde oluşturduğu farklı algılama biçimleriyle günlük yaşama adapte olurken, izleyiciyi de farklı tasarım sorgulamaları içerisine çekmektedir. Bu araştırmayla birlikte Mapping’in, dijital sergileme biçimlerine yapmış olduğu katkı örnekler üzerinden incelenecek ve bu yeni sergileme biçiminin günümüz sanatını taşıdığı nokta gözler önüne serilecektir. Araştırmanın yöntemi literetür taraması ve betimsel analizdir. Araştırmanın yeni bir kavram olan mapping tasarımını tanıtması, farklı tekniklerle melez bir dil yaratan dijital tasarım anlayışına ilgi duyan araştırmacı ve tasarımcılara kaynaklık edeceği düşünülmektedir.

Transformation is a typical motive for epic folklore texts. It appears as metamorphosis (change of the shape). As a folklore motive, the transformation has many types and shapes in the Azerbaijani folklore. The study of this motive firstly requires to approach to it in the context of mythological semantics, as the transformation motive is based on the transformation formula specific for the mythical thought. It happens in the form of the changing of their shapes by the personages in folklore texts, i.e. changing of their external appearances, transformation from one being into another being, and transformation from one cover into another one (metamorphosis). Transformation is firstly a motive specific for folklore texts. In this motive, the nation’s mythical beliefs are reflected. Transformations in folklore texts derive from natural transformations. When people saw the changes in nature, they thought that nature was alive and believed that all beings in nature had spirits. Transformation is also a cosmogonic genesis act. As known, in Azerbaijani myths, legends and tales, the motive of transformation of human beings, in particular girls and women into birds, stones or animals, and the motive of transformation in the generation of other beings are widely used. Let’s see the text of a legend: “While a daughter-in-law washes her hairs, her father-in-law comes in and the daughter-in-law feels ashamed. The girl transforms into a bird with the comb on her hairs. But she fails to fly far away”. This transformation is a cosmogonic genesis case. That is, here, a bird (hoopoe) generates from the human being (daughter-in-law). As the father-in-law sees his daughter-in-law while she washing her hairs, when being with an open head or naked, the daughter-in-law does not want to show her face again due to her shyness and turns her face to the sky and begs for becoming “a bird”, “a stone”. The desire of the daughter-in-law comes true. She transforms into “The Rocks of Bride”, a stone, a hoopoe with a comb on her head, a partridge with hennaed hands. So, the cosmogonic genesis occurs. The transformation also is an act of mediation, that is, changing the shape to transit from one space (world) to another one in the practice of shamans (gam-shaman, darvish), one of the behavioral forms specific for trixter characters in myth-folklore texts, turning, i.e., return of a character to his/her original shape, a cosmogonic genesis act, and a mechanism of dying-reviving (changing of the status) and travestism (changing of the sex) in transition rituals. The Azerbaijani folklore is rich enough with examples discussing the issue that live beings were generated from the transformation of live beings into lifeless ones and lifeless beings into another lifeless beings, nature objects were generated as a result of transformations occurred under these conditions. We can give the facts of transformation into gold, a house with silver columns, palace, needle, carpet, stick and etc. or viceversa as examples to the genesis of the world of subjects (items). And the transformation into geographical objects covers examples of transformation into a stone, mountain, hill, land, sea, lake, spring, river, fire and etc.
Transforming To Stone In Azerbaijani Folklore Texts